Primary closure of isolated sternal cleft in a 10-day-old-girl - Gulan Maree; Bardisan Gawrieh; Waseem Shater; Aras Abdo; Mhmmad Nassif; Kumait Issa; Ammar Omran (Elsevier, 2022)
Sternal cleft is a rare congenital malformation resulting from a fusion failure of the sternum and often patients have no clinical signs at birth. The defect is usually divided into partial or complete forms and is often accompanied by other anomalies. We herein report a case of upper sternal cleft that was repaired in the neonatal period by primary closure after partial thymectomy. The patient was discharged 9 days after the operation with good condition and normal respiratory movements. Sternal cleft is a rare case, with little more than 100 cases published worldwide.